Effect of Mg Doping on the Electrical Performance of a Sol-Gel-Processed SnO2 Thin-Film Transistor - Won-Yong Lee (Electronics, 2020)
Sol-gel-processed Mg-doped SnO2 thin-film transistors (TFTs) were successfully fabricated. The effect of Mg concentration on the structural, chemical, and optical properties of thin films and the corresponding TFT devices was investigated. The results indicated that an optimal Mg concentration yielded an improved negative bias stability and increased optical band gap, resulting in transparent devices. Furthermore, the optimal device performance was obtained with 0.5 wt% Mg. The fabricated 0.5 wt% Mg-doped SnO2 TFT was characterized by a field effect mobility, a subthreshold swing, and Ion/Ioff ratio of 4.23 cm2/Vs, 1.37 V/decade, and ~1 × 107, respectively. The added Mg suppressed oxygen-vacancy formation, thereby improving the bias stability. This work may pave the way for the development of alkaline-earth-metal-doped SnO2-based thin-film devices.